Content Analysis: Portrayals of Partner Aggression In the Novel "It Ends With Us" - Brigitta Jocelyn Septiandra; Kunto Adi Wibowo; Ikhsan Fuady (Metacommunication: Journal of Communication Studies, 2024)
Gender-based aggression or violence in society can happen to anyone, at any time, and by anyone who commits it. There are several factors that cause physical aggression. One of the novels by Colleen Hoover, namely It Ends With Us, has elements of physical aggression in it. Therefore, this research aims to determine the gender of the perpetrator of aggression, the depiction of the type of aggression in the novel, and the relationship between the type of aggression and how the target responds to the aggression. The population in this study were all chapters or acts in the novel. Researchers used census sampling techniques and produced all 36 chapters as research samples. This research involved two coders for the research process through coding sheets and coding books. Data analysis carried out was an inter-coder reliability test, descriptive analysis, chi-square test, and binary logistic regression test using the SPSS version 25 application. The results of the study showed that there were several categories that dominate and describe aggression, as well as the relationship between aggression and the target response in the novel "It Ends With Us".